A cross-sectional study exploring the positive aspects of caregiving in opioid dependence and its relation with quality of life, social support, and caregivers’ burden - Priyanka Saha; Sayan Saha; Gauri Shanker Kaloiya; Siddharth Sarkar (Indian Journal of Psychiatry)
Background and Aims: Despite a large body of research linking caregiver burden and social support in substance dependence, positive aspects of caregiving in these disorders have received very minimal attention. This exploratory observational study aimed to assess the positive aspects of caregiving for opioid dependence and evaluate the association of these positive aspects with caregiver quality of life, burden, and social support. Methods: This cross-sectional study included 199 caregivers of patients with opioid dependence recruited through purposive sampling. Participants were assessed using the Scale for Positive Aspects of Caregiving Experience (SPACE), World Health Organization Quality of Life–BREF version, Family Burden Interview Schedule (FBIS), and Social Support Questionnaire. Results: Of the 199 caregivers recruited, a majority of the caregivers were middle-aged women. About two-thirds of the patients were currently using opioids (n = 135, 67.8%), while the remaining were abstinent. Among the SPACE domain scores, the mean was highest for motivation for the caregiving role (2.07), which was followed by self-esteem and social aspect of caring (2.04), caregiving personal gains (1.76), and caregiver satisfaction (1.65). Caregivers of patients currently abstinent experienced greater positive aspects of caregiving (SPACE mean item score 2.57 versus 1.62, P < 0.001), and lesser burden (FBIS mean score 13.4 versus 29.3, P < 0.001). Conclusion: Positive aspects of caregiving can be potentially utilized for better caregiver engagement in treatment and improved caregiver outcomes.